Pengembangan Antarmuka Pengguna (User Interface) Sistem Pengelolaan Beasiswa Berbasis Website dengan Pendekatan Cognitive Walkthrough - Tasya, Selviana; Setyantoro, Dwipo (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2025)
An effective user interface (UI) is crucial in a web-based scholarshipmanagement system to ensure a good user experience and easy accessibility toinformation. However, many users still encounter difficulties using the existingsystem, necessitating a better design. This study aims to evaluate and improve theuser interface of the scholarship management system using the CognitiveWalkthrough approach. The Cognitive Walkthrough approach is used to identifyusability issues in the user interface. A prototype of the design solution was thentested through usability testing involving seven evaluators and five different taskscenarios using Maze. The results show that all evaluators were able to completethe task scenarios with a category 1 rating (no issues), although four evaluators experienced minor issues in task scenarios 1 and 2. Evaluators were slightlyconfused when searching for the latest requirements information and the ineffectiveuse of buttons. By implementing the suggested improvements based on the findingsfrom the Cognitive Walkthrough, the user interface in the scholarship managementsystem can be significantly enhanced, facilitating users in accessing the requiredinformation.